Monocrotaline-mediated autophagy via inhibiting PI3K/AKT/mTOR pathway induces apoptosis in rat hepatocytes - Guo, Yazhou; Yuan, Yang; Wang, Ruibo; Bai, Jun; Jia, Yanqing; Qiu, Xinxin; Niu, Huafeng; Li, Long; Luo, Yan; Zhao, Baoyu; Zhang, Zhencang (Frontiers in Pharmacology, 2024)
Monocrotaline (MCT), a major pyrrolizidine alkaloid, is well-known for its high liver toxicity. Dysregulation of autophagy induced apoptosis can lead to various liver diseases, including those induced by chemical compounds. Therefore, we aim to explore whether autophagy might serve as a potential strategy for addressing liver apoptosis caused by MCT. In primary rat hepatocytes (PRHs), MCT significantly increased the number of autophagosomes and the expression levels of LC3II, Becline-1, and Atg5, while it decreased the expression of p62 in a concentration-dependent manner at doses of 100, 200, 300, and 400 μM. Western blot assays revealed MCT inhibited the phosphorylation levels of the PI3K/AKT/mTOR pathway. To elucidate the role of autophagy in mediating MCT-induced apoptosis, we further pretreated PRHs with the autophagy agonist Rapamycin and the inhibitors Bafilomycin A1 and Chloroquine, respectively, and assessed the apoptosis of PRHs induced by MCT. The results displayed that Rapamycin increased the apoptosis rate and the expression of cleaved caspase-3, whereas Bafilomycin A1 and Chloroquine reduced the apoptosis and the expression of cleaved caspase-3 in PRHs. This study 删除了: Bafilomycin 30 删除了: Bafilomycin 31 2 confirms that autophagy enhances PRHs apoptosis induced by MCT. In summary, this study demonstrates that MCT-induced autophagy via inhibition of the PI3K/AKT/mTOR pathway can lead to apoptosis in PRHs.